Implementasi Kurikulum Merdeka di Lembaga Pendidikan Pesantren dalam Meningkatkan Mutu - Lailiyah, Siti; Imami, Agus Sulthon (LP. Ma'arif Janggan Magetan, 2023)
This research explores the implementation of the Merdeka Curriculum at the Islamic Studies Institute, a pesantren (Islamic boarding school) in Indonesia. Utilizing a qualitative approach involving observation, interviews, and documentation, the study subjects include the institution's head and teaching staff. The research context revolves around the existence of pesantren as Islamic educational institutions with a longstanding presence in Indonesia, influenced by the majority of the population adhering to Islam. The study aims to comprehend the planning, implementation, and evaluation of the Merdeka Curriculum in pesantren. Given the backdrop of the dynamic changes in curricula in Indonesia, from KTSP (School-Based Curriculum) to the 2013 Curriculum, this research highlights the role of the Merdeka Curriculum in influencing learning patterns and enhancing the quality of education. The findings indicate that the implementation of the Merdeka Curriculum requires careful planning and ongoing impact evaluations. The primary focus of the research is on the perspectives of the institution's head and teaching staff regarding the Merdeka Curriculum, as well as their efforts in curriculum design, implementation, and evaluation. The research concludes by emphasizing the importance of effective management in adopting the Merdeka Curriculum in pesantren, ensuring a significant improvement in the quality of education in line with the curriculum's objectives.